The Influence of Transformational Leadership, Eployee Digital Competency, And Perceived Organizational Support on Eemployee Performance With Job Satisfaction as a Mediation Variable - Yamin, Bun; Nur Fadilah, Mursidah (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2024)
Optimal employee performance can increase productivity and reduce the level of errors at work. So it is necessary to know what factors can influence employee performance which are mediated by employee job satisfaction in order to improve employee performance. In this research, the factors examined are Transformational Leadership, Employee Digital Competence, and Perceived Organizational Support. The research method used in this study is a quantitative approach, with a sample of 100 respondents. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS version 3 software. The findings of this study are that Transformational Leadership has a significant effect on Employee Performance. Digital Competence does not have a significant influence, while Perceived Organizational Support contributes positively to Employee Performance. Job satisfaction was identified as a significant mediator between these variables, except for the influence of Digital Competence and Perceived Organizational Support on Employee Performance.